Integrating information communication technology (ICT) into secondary school teaching process in Nigeria (2018)
The problem of Information and Communication Technology (ICT) teaching, availability, utilization, evaluation and policy implementation among public secondary schools is new in Nigeria has been a subject of concern to stakeholders. Nigeria joining the global ICT scramble has formulated policies that ensures ICT an examinable subject at the Senior Secondary School level in Nigeria. The process of implementing this new policy is of interest to this study which investigated the integration of ICT teaching into Nigerian secondary schools teaching process. The survey research design which drew four research questions and two hypotheses was adopted. The total population consisted of secondary schools in Oyo state with Ibadan North Local Government Area sampled. Simple random sampling technique was adopted to select 15 out of the 47 secondary schools and 172 teachers as respondents. An instrument titled 'ICT integration and teaching process Questionnaire' (ICTYTQ r=0.61) was validated by colleagues in the Faculty of Education of the University of Ibadan. Findings indicated that a significant relationship existed between Availability of ICT resources and ICT teaching process with r-0.0118;p<0.05 while Teacher quality and students learning outcome in ICT teaching process did not give a significant result r=0.089;p<0.05. The study recommended that more ICT teacher specialist be recruited and also there should be provision of in-service and refresher courses for serving teachers.